PENGGUNAAN INSTAGRAM SEBAGAI UPAYA PROMOSI WISATA DI DE JAVASCHE BANK SURABAYA - Rosdiana Windiarti, Khofiatul (Penerbit Lafadz Jaya, 2024)
The city of Surabaya has a variety of tourist attractions ranging from natural tourism, religious tourism, culinary tourism and historical tourism. This city, which is nicknamed the city of heroes, is known for its historical tourism, one of which is De Javasche Bank Surabaya. De Javasche Bank is a cultural heritage that preserves the history of finance and banking in Indonesia. This attraction was closed due to the COVID-19 pandemic. To increase tourist visits again, De Javasche Bank is making tourism promotion efforts through Instagram social media. This research uses a qualitative approach with data collection techniques through observation, in-depth interviews and documentation which will then be explained descriptively. The research results show that De Javasche Bank, through the @de_javaschebank_surabaya account, has actively promoted its appeal on Instagram by utilizing the feeds, stories, reels, captions and hashtag features. In utilizing this feature, De Javasche Bank creates and uploads interesting and educational content.